Analysis The Effect of Emotional Intelligence on Performance Through Leadership Style and Organizational Culture as A Moderator - Putri, mentari adriaeni; Gustomo, Aurik (Jurnal Manajemen Teknologi, 2012)
AbstractPerformance are the result of a complex process, which are come from the employee (internal factors), company situation (external factors) and the company strategic efforts. Performance were able to assessed of corporate achievement objectives. The purpose is to analyzed the effect of emotional intelligence on performance through leadership style and organizational culture as moderator. Using a descriptive correlational method, this research have been conducted in the company of Pertambangan and Energi (Geothermal) in Kamojang. 205 employees selected as respondents by using proportionate random sampling. Questionaire was used as a tool in data collection method. Data analysis techniques is Multiple Regression Analysis. Emotional intelligence has a positive influence on the Performance, Emotional intelligence and transformational leadership positive effect on performance, Emotional intelligence and organizational culture affect the performance, The effect of emotional intelligence with moderation transformational and transactional leadership and organizational culture affects on performance. Organizational culture is the most dominant variable affecting performance and Transformational leadership has a small effect compared to the other three variables, that transformational leadership is considered less support for enterprises to increasing performance, thus a need to develop transformational leadership is a skill. Â Keyword : Emotional intelligence, Leadership style, Organizational Culture, Performance.